Phage display as a tool for generation of bio-therapeutic agents for breast cancer - Ferreira, Andreia Teixeira (2015)
Notch is a conserved signalling pathway, which plays a crucial role in a multiple cellular processes such as stem cell self-renewal, cell division, proliferation and apoptosis. In mammalian, four Notch receptors and five ligands are described, where interaction is achieved through their extracellular domains, leading to a transcription activation of different target genes. Increased expression of Notch ligands has been detected in several types of cancer, including breast cancer suggesting that these proteins represent possible therapeutic targets. The goal of this work was to generate quality protein targets and, by phage display technology, select function-blocking antibodies specific for Notch ligands. Phage display is a powerful technique that allows the generation of highly specific antibodies to be used for therapeutics, and it has also proved to be a reliable approach in identifying and validating new cancer-related targets. Also, we aimed at solving the tri-dimensional structure of the Notch ligands alone and in complex with selected antibodies. In this work, the initial phase focused on the optimization of the expression and purification of a human Delta-like 1 ligand mutant construct (hDLL1-DE3), by refolding from E. coli inclusion bodies. To confirm the biological activity of the produced recombinant protein cellular functional studies were performed, revealing that treatment with hDLL1-DE3 protein led to a modulation of Notch target genes. In a second stage of this study, Antibody fragments (Fabs) specific for hDLL1-DE3 were generated by phage display, using the produced protein as target, in which one good Fab candidate was selected to determine the best expression conditions. In parallel, multiple crystallization conditions were tested with hDLL1-DE3, but so far none led to positive results.